2010
DOI: 10.3144/expresspolymlett.2010.96
|View full text |Cite
|
Sign up to set email alerts
|

Affecting glass fibre surfaces and composite properties by two stage sizing application

Abstract: Abstract. The influence of sizing constituent distribution on the properties of sized glass fibres (GFs) and corresponding polypropylene (PP) composites was studied by two-stage sizing application, i.e. applying silane coupling agent and polymeric film former at separate stages and with different sequences, in comparison with one-stage sizing application usually used. Surface properties of sized GFs and transverse tensile strength of unidirectional GF reinforced composites were studied using various surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…The IFSS determined for different fiber sizings for glass fiber-epoxy systems agreed well with the macroscopic composite properties through transverse tensile and compression shear tests [8]. The adhesion strength between glass fibers and a polypropylene matrix was found to be largely influenced by both the sizing and the conditions and manner in which it was applied, as shown by Zhuang et al [9]. Several other researchers have alluded to the large influence of fiber-matrix interface strength on the mechanical properties of a textile composite [10][11][12][13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 74%
“…The IFSS determined for different fiber sizings for glass fiber-epoxy systems agreed well with the macroscopic composite properties through transverse tensile and compression shear tests [8]. The adhesion strength between glass fibers and a polypropylene matrix was found to be largely influenced by both the sizing and the conditions and manner in which it was applied, as shown by Zhuang et al [9]. Several other researchers have alluded to the large influence of fiber-matrix interface strength on the mechanical properties of a textile composite [10][11][12][13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 74%
“…Correspondingly, the R q and R max of differently sized GFs -8 -exhibited no difference and were in the range of 9.2−12.9 nm and 93.1−121.2 nm, respectively (Table 1). In addition, the R max values are close to the mean particle size of PP film former [23], this suggests that the aggregates were mainly made of PP particles.…”
Section: Surface Properties Of Sized Gfsmentioning
confidence: 72%
“…Table 1 Taking into consideration the similar topography and surface roughness for all four sized GFs, the lower θ r for GF-32 is most likely attributed to its higher sizing uptake, since it was noted previously that the GFs sized only with the same PP film former used here exihibited low θ r of 41.6 o [23]. This will be further described in next part.…”
Section: Surface Properties Of Sized Gfsmentioning
confidence: 92%
See 1 more Smart Citation
“…They also correlated fibre tensile strength and surface roughness with Griffith fracture predictions. Zhuang et al [104] have reported on the application of PP compatible sizing using dual applicators.…”
Section: Combined Multiple Analysis Techniquesmentioning
confidence: 99%